PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA SEKTOR BARANG DAN KONSUMSI - Christina Christina Christina; Juniarti Juniarti Juniarti (Business Accounting Review, 2016)
The objective of this resech was to find out whether or not Corporate Social Responsibility (CSR) had influence on the firm value, in which the CSR variable was measured based on the Gloal Reporting Initiative Index 3.1 standart, while firm value was measured by using Tobin’s Q. The sample was taken form the observation of 124 companies in Consumer Goods Industry sector within 2009-2013. The result of this reserch showed that Corporate Social Responsibility had no significant influance on the firm value, while the other control variable, namely firm size had significant influence on the firm value. But market share and debt to equity ratio control variables had no impact on the firm value.